Welfare Abuse as a Challenge for the Sustainable Development of the Welfare State - Jurek, Łukasz (Publishing House of Wroclaw University of Economics and Business, 2024)
This study presents selected elements of the research project entitled ‘Social, economic and cultural determinants of the use of welfare benefits: an analysis of the problem in the context of benefit morality’, carried out by a research team from the Department of Sociology and Social Policy at the Wroclaw University of Economics and Business. The topic is welfare abuse. The author discussed the theoretical concept of this problem, methodological issues related to its study, as well as the results of various empirical studies.
Jurek, Ł. (2024). Welfare Abuse as a Challenge for the Sustainable Development of the Welfare State. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 92-108). Publishing House of Wroclaw University of Economics and Business.
Keywords: welfare state; benefit morality; welfare abuse